You, the leader (Boston, Massachusetts : Harvard Business Review Press, 2022)
"It's time for female leaders to stand out. Women often aren't seen for their leadership potential. We face a double bind, forced to choose whether to be liked or respected, while neither one alone is enough to secure a seat at the table. It's up to organisations to change, but until then, what's an aspiring female leader to do? You, the Leader tackles the obstacles you face as you chart your path to the top, from not getting credit for your work to feeling unseen to being subjected to unfair biases and expectations. Filled with advice, tips, and relatable conversations, this book will help you better understand how you can remain authentic while showing yourself as a valued leader in your organisation"--Publisher's description.
"Women at work, inspiring conversations, advancing together"--Title page.
Includes bibliographical references (pages 185-191) and index.
Keywords: Businesswomen; Leadership; Success in business; Leadership; Leadership